JURIDIC ANALYSIS OF USED CLOTHES CONSUMER BASED ON ARTICLE 4 CONSUMER PROTECTION AND ISLAMIC LAW PERSPECTIVE - Sugiharto Sugiharto; Andi Aina Ilmih (Jurnal Pembaharuan Hukum, 2019)
This research focuses on the form of legal protection for used clothing consumers based on Article 4 of Law Number 8 of 1999 concerning consumer protection and analyzes the impact of the use of used clothing by the community in the city of Semarang, related to the Thaharah aspects in Islamic Law.To achieve this goal, researchers used a sociological juridical approach with data collection techniques in the form of library research and field studies by conducting direct interviews with relevant parties in connection with this research. The data obtained were then processed and analyzed by descriptive qualitative.The results showed that the form of legal protection for used clothing consumers in the Consumer Protection Act under Article 4, namely the right of consumers to get comfort, security, and safety. This is closely related to the obligations of business actors in providing true, clear and honest information about the conditions and guarantees of goods and/or services; and the need for guidance and supervision by the government. The impact caused by used clothing is negative impact and positive impact for used clothing consumers, both in terms of economic, social and public health in Indonesia. Although in an Islamic perspective, it is recommended that people prioritize aspects of thaharah (cleanliness) as Allah SWT requires every Muslim to purify in accordance with the criteria of Allah and His Prophet.